Community based mentors and journey guides: a transformative learning approach to social work education - Lorenzetti, Liza; Halvorsen, Jeffery; Dhungel, Rita; Lorenzetti, Diane; Oshchepkova, Tatiana; Haile, Lemlem; Biscette, Krishma (My University, 2019)
Critical pedagogy is congruent with the social work discipline, which is engaged, people-focused, and centers on social justice, liberation and human rights. While there is growing recognition of the importance of better preparing social work students to engage in critical, anti-oppressive practice, students have limited opportunities for transformative learning experiences within community settings, outside of official practicums. Masters of Social Work students pursuing a specialization in international and community development (ICD) at a Canadian university were matched with community Journey Guides who provided mentorship and opportunities for students to become involved in community-based social justice initiatives. This article presents the eight-step experiential framework that was used as a pedagogical tool to support student learning, and the results from the program’s evaluation with the first student cohort. Using surveys and focus groups, the study found the guiding relationship was characterized by acceptance, friendliness, encouragement, and motivation. Students engaged in critical dialogues with Guides, gained community development experience and skills and enhanced their social justice knowledge.
Keywords: transformative learning; social work education; journey guides; critical pedagogy